Development of a Metabolically Stable Neurotensin Receptor 2 (NTS2) Ligand - Held, Cornelia; Plomer, Manuel; Hübner, Harald; Meltretter, Jasmin; Pischetsrieder, Monika; Gmeiner, Peter (ChemMedChem, 2013)
Subtype-selective neurotensin receptor2 (NTS2) ligands can be used as molecular probes to investigate the physiological role of neurotensinergic systems and serve as lead compounds to initiate the development of drugs for the treatment of tonic pain. Starting from our recently described NTS2 ligand 1, structural variants of type 2 were synthesized to further improve binding affinity and selectivity to gain metabolic stability. The peptide-peptoid hybrid 2b showed excellent NTS2 binding affinity (K=2.8nM) and 22000-fold selectivity over NTS1, as well as metabolic stability over 32h in a serum degradation assay. Employing a MAPK-driven luciferase reporter gene assay and an IP accumulation assay, the neurotensin mimetic 2b displayed respective inhibitions of constitutive activity exceeding 4.3- and 3.9-fold that of the inverse agonist activity of the endogenous ligand neurotensin. © 2013 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.

Development of Covalent Ligand-Receptor Pairs to Study the Binding Properties of Nonpeptidic Neurotensin Receptor 1 Antagonists. - Kling, Ralf; Plomer, Manuel; Lang, Christopher; Banerjee, Ashutosh; Hübner, Harald; Gmeiner, Peter (ACS Chemical Biology, 2016)
The neurotensin receptor NTS1 has been suggested to be of pharmaceutical relevance, as it was found to exert modulatory effects on dopaminergic signal transduction and to be involved in tumor progression. Rational drug design of NTS1 receptor ligands requires molecular insights into the binding behavior of a particular lead compound. Although crystal structures of NTS1 have revealed the molecular determinants of peptide-agonist interactions, the binding mode of small-molecule antagonists remains largely unknown. Employing a disulfide-based tethering approach, we developed covalently binding molecular probes. The ligands 1 and 2 are based on the pharmacophore of the nonpeptidic NTS1 antagonist SR142948A, allowing the formation of a disulfide bond to an engineered cysteine residue of NTS1. The position of the covalent bond between Cys127(2.65) and the ligand was used to predict the binding mode of the covalent antagonist 1 and its parent compound SR142948A by molecular dynamics simulations.

Discovery of highly potent and neurotensin receptor 2 selective neurotensin mimetics - Einsiedel, Jürgen; Held, Cornelia; Hervet, Maud; Plomer, Manuel; Tschammer, Nuska; Hübner, Harald; Gmeiner, Peter (Journal of Medicinal Chemistry, 2011)
The neurotensin receptor subtype 2 (NTS2) is involved in the modulation of tonic pain sensitivity and psychiatric diseases and is, therefore, regarded as a highly attractive pharmacological target protein. Aiming to discover NTS2 selective ligands, we herein describe the identification of screening hits and the chemical synthesis of structural variants leading to the highly potent and NTS2 selective peptide-peptoid hybrids of type 3. The neurotensin mimetics 3a and 3e-g incorporating an N-(4-hydroxyphenethyl)glycine substructure exhibit single digit nanomolar affinity (K = 4.3-8.8 nM) and 1900-12000 fold selectivity over the neurotensin receptor subtype 1 (NTS1). According to functional experiments, the test compounds 3a and 3e-g displayed an inhibition of constitutive mitogen-activated protein kinase (MAPK) activity exceeding 2.6-4.6 times the inverse agonist activity of the endogenous ligand neurotensin. © 2011 American Chemical Society.

Radical arylation of tyrosine and its application in the synthesis of a highly selective neurotensin receptor 2 ligand - Pratsch, Gerald; Unfried, Johannes F.; Einsiedel, Jürgen; Plomer, Manuel; Hübner, Harald; Gmeiner, Peter; Heinrich, Markus (Organic & Biomolecular Chemistry, 2011)
A small library of Fmoc-protected 3-arylated tyrosines was created by radical arylation. The new building blocks were successfully applied in the synthesis of two novel neurotensin receptor ligands. Both isomers showed high affinity for the human NTS2 receptor with K values in the nanomolar range. Interestingly, subtype selectivity strongly depends on the configuration of the peptide in position 11. Isomer (11R)-3 displayed an excellent preference for NTS2 compared to NTS1. © 2011 The Royal Society of Chemistry.